Perencanaan Perbaikan Tempat Penyimpanan Sementara (TPS) Limbah B3 PT. X Berlokasi di Kawasan Industri SIER - Euis Nurul Hidayah; Steven Pohan (Prosiding ESEC, 2023)
PT. X is a company engaged in product packaging printing. The condition of the temporary storage area (TPS) for B3 waste at this company is not in accordance with applicable regulations. This study aims to redesign the hazardous waste TPS building to comply with government regulations, namely PP No. 22 of 2021 and also PermenLHK No. 6 of 2021, the research begins with collecting data on the types, characteristics, and also the amount of B3 waste generated from the production and maintenance processes at PT X. The data that has been obtained is then processed using various calculations to further design buildings in the Autocad software application . Based on data processing on the generated B3 waste, the total number of containers needed is 35 drums for B3 liquid waste and used rags and then 12 pallet boxes for B3 solid waste. The planned TPS building has dimensions of 15.55 m in length, 8 m in width and 3 m in height. The B3 waste TPS building is equipped with 6 air vents, 16 lamps, and also 1 fire extinguisher and the number of containers used is 35 drums for B3 liquid waste and used rags; then 12 pallet boxes for B3 solid waste